Effects of plasma treatments of polypropylene adhesive joints used in the automotive industry. (June 2022) - Ciardiello, Raffaele; D'Angelo, Domenico; Cagna, Laura; Croce, Alessandro; Paolino, Davide Salvatore
Plasma treatment has been used in recent years to activate the surfaces of adhesive substrates and thus as an adhesion promoter between adhesive and substrates. The use of plasma treatments is widely adopted in the automotive industries especially for polymers that present low surface energy, such as polypropylene. In this work, polypropylene substrates used in the automotive industries have been treated with two different techniques: vacuum and atmospheric plasma. Then, polyurethane and methacrylate adhesives have been used to bond single lap joints (SLJs). Typically, these two adhesives cannot bond polypropylene substrates without surface treatments. An experimental plan has been designed to investigate the process parameters that can increase the functional polar groups (FPGs) maximizing the adhesion strength. Besides the types of plasma, two different gas carriers (air and nitrogen) and different treatment times have been investigated. The substrates, treated and not treated, have been assessed through scanning electron microscopy, energy-dispersive X-ray analysis, and Fourier-transform infrared spectroscopy to quantitatively assess the increment of FPGs after the different treatments. The experimental plan shows that the atmospheric plasma can improve the surface of the substrates by using a smaller time. Mechanical tests on SLJs show that methacrylate and polyurethane cannot bond polypropylene substrates without the plasma treatment. On the other hand, the treated substrates can form a strong bonding with the adhesive since all SLJs exhibit a substrate failure. Mechanical tests have been also carried out after three different aging cycles showing that the adopted plasma treatment is not affected by the aging cycles.